An assessment of the effects of COVID-19 pandemic on Kenya's trade - Maureen Were; Kethi Ngoka (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
We examine the impact of the COVID-19 pandemic on Kenya's foreign trade using quarterly trade data for the period 2019 to the second quarter of 2021. The exploratory analysis shows that growth of Kenya's merchandise exports remained resilient, largely supported by traditional exports of tea and horticultural products. However, the service exports, particularly travel and transport services, were adversely affected. Heterogeneous effects of the COVID-19 pandemic on exports are observed across sectors. The collapse of international oil prices in 2020 led to significant savings on imports. Given the disruptions to supply chains, some shift to alternative non-traditional markets for both exports and imports was witnessed. A differentiated speed of export recovery is observed. A long-term recovery strategy for the service exports is needed, given ongoing pandemic effects. Increased diversification of exports and markets, coupled with increased value addition and deepening of regional trade integration, is bound to boost exports and enhance resilience.
Keywords: F1; F10; F19; 330; trade; Kenya; exports; COVID-19; pandemic